Post-Coal Mining Reclamation Land Sustainability Study in Tebo Regency - Hendriyanto; Dedi Hermon; Eri Barlian; Iswandi Umar; Nur Efendi (Jurnal Penelitian Pendidikan IPA, 2023)
This research was conducted at one of the coal mines in Tebo Regency, namely PT. Asia Multi Investama. The technique for determining respondents was determined by purposive sampling with a sample size of 54 people. The data analysis techniques used are laboratory analysis (water and land), descriptive analysis (to determine the reclamation model) and sustainability index measurement using multidimensional scaling (MDS) from the three dimensions of sustainability analyzed, namely the social dimension and the economic dimension. and ecological dimensions. The results of soil and water laboratory analysis show a decline in soil and water quality. The results of observations of vegetation in the field also showed a decrease in plant growth. Management of post-mining reclamation land PT. The current Asia Muti Investama is quite sustainable with an Appraisal Post Coal Mining Sustainable (APCMS) score of 55.27 on a scale of 0 -100. The reclamation model that can be applied is the agroforestry reclamation model with the agrosilvofishery system. The leading tree commodities are rubber and palm oil. For fisheries, this is a place for fish breeding in former mining ponds (voids) with types of tilapia, goldfish and catfish. Sensitive factors as levers that influence the sustainability of PT's former coal mining land. Asia Multi Investama.